Study the expression level of beta 2 microglobulin gene on hepatitis C patients before and after treatment with interferon - Baghdad Science Journal (Baghdad Science Journal, 2012)
This study has been carried out to evaluate the expression level of beta 2 microglobulin gene on patients infected by hepatitis C virus before and after treatment with interferon. The study included 117 hepatitis C patients comprising as 63 pre-treated patients, the range of age was between 20-65 year with a mean age of 48.12 ± 16.1 and 54 post-treated patients with age range was between 23-63 year with the mean of 46.1 ± 18.1. Also it was found that more than half of patients were located within third and fourth decade i.e. 30-49 year, with a percentage of 52.4% and 55.6 % for pre-treatment and post-treatment patients respectively. Moreover , regarding both groups, males are more than females with the ratio of ( 3.2:1) among pre-treatment group and 2:1 among post-treatment group. Further , It has been found that the concentration of ?2 microglobulin was (3.425±0.943mg/L) among pre-treatment group and (1.860±0.723 mg/L) among post-treatment group with significant correlation (P=0.05). Besides that , in the present study ,It has been found the concentration of ?2 microglobulin was decrease after treatment from (3.425±0.943 mg/L) to (1.860±0.723mg/L) which was statistically significant (P=0.05) , Thus ?2 microglobulin can be used as a supporting marker of responsiveness to treatment with interferon in hepatitis C patients as well as indicator for monitoring the disease progression.